2015
DOI: 10.1111/eea.12367
|View full text |Cite
|
Sign up to set email alerts
|

Material affects attack rates on dummy caterpillars in tropical forest where arthropod predators dominate: an experiment using clay and dough dummies with green colourants on various plant species

Abstract: International audiencePredation can be one of the key factors that determine abundance in insect herbivore communities, and drive evolution of body size, and anti-predator traits, including crypsis. Population dynamics and selection pressures will depend on the identity of dominant predators in the system, and these may vary substantially among habitats. Arthropods emerge as chief predators on caterpillars in the understorey of non-montane tropical forest, whereas birds dominate elsewhere. In a tropical forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 66 publications
2
70
2
Order By: Relevance
“…While parasitoids were the only natural enemy group readily identifiable using real prey, identified natural enemies of artificial caterpillars (median = 3 per study) included vertebrates (birds n = 40; mammals n = 14; reptiles (Posa et al ., ), as well as invertebrates, among them ants ( n = 12), predatory wasps (Faveri et al ., ; Jordani et al ., ; Molleman & Safian ; Sam et al ., ,b), parasitoid wasps (Tvardikova & Novotny, ; Howe et al ., ), other insects, predatory bugs, cockroaches (Molleman et al ., ), and spiders (Posa et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…While parasitoids were the only natural enemy group readily identifiable using real prey, identified natural enemies of artificial caterpillars (median = 3 per study) included vertebrates (birds n = 40; mammals n = 14; reptiles (Posa et al ., ), as well as invertebrates, among them ants ( n = 12), predatory wasps (Faveri et al ., ; Jordani et al ., ; Molleman & Safian ; Sam et al ., ,b), parasitoid wasps (Tvardikova & Novotny, ; Howe et al ., ), other insects, predatory bugs, cockroaches (Molleman et al ., ), and spiders (Posa et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…In line with the study by Roslin et al (), we found that attack rates by arthropod predators on model prey decreased from low to high latitudes. The tropics are habitats with a very high abundance and diversity of arthropod predators, especially ants and wasps, which dominate the predator communities in tropical forest understoreys (Floren, Biun, & Linsenmair, ; Sam et al, ). More than a half of the studied ant species attack large caterpillars (Floren et al, ), and experiments with live insect prey have demonstrated higher predation rates by ants in the tropics than in temperate forests (Jeanne, ).…”
Section: Discussionmentioning
confidence: 99%
“…This may lead to an underestimation of bird predation in tropical forests, where both bird enclosures (van Bael, Brawn, & Robinson, ) and model caterpillars (Loiselle & Farji‐Brener, ) revealed higher rates of bird predation in the top canopy than in the lower forest strata. Model caterpillars placed in tropical forest understoreys sometimes showed no signs of bird predation (Sam et al, ). These results may be at least partly due to the higher abundance of natural prey in the top canopy than in the understorey of a tropical forest (van Bael et al, ; Basset et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these methods are being increasingly used (Meyer et al, 2015;Sam et al, 2015). However, the influence of methodological procedures on the detection of predation responses is still poorly known ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the effects of the type of prey Molleman et al, 2015) and the time of exposure of preys (e.g. Loiselle et al, 2002;Molleman et al, 2015;Sam et al, 2015) should be better explored. Providing different preys and using different exposure times to predation can impede the comparison of results, which may cause confusion in detecting general ecological patterns of predation and pest control.…”
Section: Introductionmentioning
confidence: 99%